Scalp pruritus: Review of the pathogenesis, diagnosis, and management - Ploysyne Rattanakaemakorn (2020)
© 2019 Ploysyne Rattanakaemakorn and Poonkiat Suchonwanit. Scalp pruritus is a frequent problem encountered in dermatological practice. This disorder is caused by various underlying diseases and is a diagnostic and therapeutic challenge. Scalp pruritus may be localized to the scalp or extended to other body areas. It is sometimes not only associated with skin diseases or specific skin changes, but also associated with lesions secondary to rubbing or scratching. Moreover, scalp pruritus may be difficult to diagnose and manage and may have a great impact on the quality of life of patients. It can be classified as dermatologic, neuropathic, systemic, and psychogenic scalp pruritus based on the potential underlying disease. A thorough evaluation of patients presenting with scalp pruritus is important. Taking history and performing physical examination and further investigations are essential for diagnosis. Therapeutic strategy comprises removal of the aggravating factors and appropriate treatment of the underlying condition. All treatments should be performed considering an individual approach. This review article focuses on the understanding of the pathophysiology and the diagnostic and therapeutic management of scalp pruritus.